ARBEJDE ER LIVET: Refleksioner over „det grænseløse arbejde“ - Baarts, Charlotte (Tidsskriftet Antropologi, 2005)
The boundaries between working life and other life are shifting. The post-modern employee has become personally responsible for organising his own work in both time and space. This may lead to the experience of increased mobility between working life and other life. Flexible working hours, as well as an overlap between working activities and leisure activities, veil the distinction between working time and other time. Furthermore, individuals experience time differently, connecting time not only to linearity but also to events and tasks at work. The physical frames of work are also undergoing dramatic changes. New technologies enable the individual to carry out his job anywhere and at any time. Work is not only performed at specific workplaces, but also at home, in trains, planes - almost anywhere. As such tasks, rather than time and place, have become the organising principle when it comes to the relationship between working life and other life. And task-orientation makes it difficult to distinguish between the categories “working life” and “other life” in practice. In fact, work is not just a part of life. Work becomes life, just as life becomes work.